X-factor estimation and controversies: the case of Lima´s airport - Defilippi, Enzo (2013)
In theory, X-factor regulation provides better incentives for cost reduction than previously widely-used rate-of-return regulation. However, a deeper look into how this factor is effectively estimated shows the regulator enjoys a great deal of discretion, especially when selecting the methodologies used to estimate its components. This paper describes how the X-factor is estimated in Peru and analyzes the main controversies (both theoretical al practical) that arose when the X factor for the country’s main airport was estimated. Conclusions are the following: i) careful planning of the concession process reduces the probability of unnecessary controversies when the X factor is estimated retrospectively, since this methodology requires data that needs to be collected at the time of the concession; ii) cost of capital estimation is a main source of controversies due to the subjective criteria used in its calculation and its impact in the final result; and, iii) transparent procedures improve the legitimacy of regulatory decisions, especially in contexts of limited public resources and weak institutions, typical of developing countries.